Sztuczne zapłodnienie z perspektywy bioetyki rodziny - Mariusz Ciszek (Studia Ecologiae et Bioethicae)
In this article I am going to present the moral problems of artificial insemination from the new discipline- bioethics of a family perspective, this branch of bioethics deals with the moral appreciates of contemporary technical civilization influence function of the family’s environment, the author takes for granted that health and life are an individual right of every man, which has the social aspect too, connected with family. It results from a fact that all disturbances in a family’s environment have a negative influence on the life and function of an individual, which also contribute to regress of social potential. A family is an unconditional right of every man, which should be protected. In this publication I am going to present the problem of artificial insemination, which constitutes an integral part of the bioethics of a family, the main criterion of moral appreciation is a right of a child.